2007
DOI: 10.1136/bjsm.2007.036335
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation in the elite athlete and type of sport

Abstract: Elite athletes who practice water sports have mild neutrophilic inflammation, whether or not asthma is present, related to the degree of bronchial hyper-reactivity and the duration of training in pool water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
4
37
0
6
Order By: Relevance
“…A mixed type of airway inflammation, mostly made up of neutrophils and eosinophils, has been observed in swimmers and cross-country skiers [4][5][6][7]. However, whether such airway inflammation is associated with AHR in athletes has to be further documented [5][6][7].…”
mentioning
confidence: 99%
“…A mixed type of airway inflammation, mostly made up of neutrophils and eosinophils, has been observed in swimmers and cross-country skiers [4][5][6][7]. However, whether such airway inflammation is associated with AHR in athletes has to be further documented [5][6][7].…”
mentioning
confidence: 99%
“…Helenius et al [38] found out that bronchial hyperreactivity was more present in swimmers (48%) than in non swimmers (16%) and, after analysing the characteristics of the subjects' sputum noticed that the amount of eosinophil and neutrophil leukocytes was Potential negative effects of chlorinated swimming pool attendance on health of swimmers and associated staff pro-inflammatory reactions like allergies) than those without symptoms, as well as a significantly higher bronchial hyperreactivity to histamine. In contrast, Belda et al [10] found that the inflammation could be mediated by neutrophils, rather than eosinophils, and could be related to the duration of training, perhaps due to exposure to chlorine derivatives.…”
Section: Effects On Competition Swimmers Technical Staff and Operatomentioning
confidence: 92%
“…2) [17]. Нейтрофильный характер мокроты отмечен также у пловцов, причем содержание нейтрофилов корре лировало с бронхиальной гиперреактивностью и про должительностью спортивной карьеры [8].…”
Section: обзорыunclassified
“…В большинстве исследований не происходит четкой дифференцировки пациентов с астмой в сочетании с БФН и лиц с БФН без астмы. Давно известен факт значительно большей распро страненности БФН среди спортсменов атлетических видов спорта высоких достижений, в особенности среди тех из них, кто соревнуется на длинные дис танции [7,8]. В таблице представлена распростра ненность БФН при различных видах спорта.…”
unclassified